Analysis of Volatile Compounds in Baby Banana Peel and Pulp (musa Acuminata AA Simmonds Cv. Bocadillo) in Relation to the Hyperpigmentation Phenomenon. Issue 3 (2nd July 2020) - Pino, Jorge A.; Castro-Benítez, Marcela; Winterhalter, Peter
ABSTRACT: Baby banana ( Musa acuminata AA Simmonds cv. Bocadillo) is cultivated in Colombia and other tropical regions. The hyperpigmentation phenomenon is the occurrence of green veins through the peels which causes that fruits are rejected in the international marketing. The aim of this study was the analysis of the hyperpigmentation phenomenon in relation to the production of volatile compounds in Baby banana peel and pulp. Volatiles profiles from pulp and peel of hyperpigmentated and control ripe samples were analyzed by GC-FID and GC-MS. The results suggest that there are no qualitative and quantitative differences in the volatile compounds between control and hyperpigmentated fruits.